Empirical Analysis of The Hysteresis Effect in Long-Term And Youth Unemployment in Türkiye Within The Framework of Regional And Demographic Dynamics (Third Sector Social Economic Review, 2025)
Unemployment is not merely a statistical indicator but a multidimensional issue that tends to become persistent, especially among vulnerable social groups. In this context, determining whether labor market shocks have temporary or permanent effects is crucial for shaping effective employment policies. This study investigates the presence of hysteresis in long-term and youth unemployment rates in Türkiye between 2006 and 2023. The dataset covers total, female, and male unemployment rates across 26 NUTS-2 regions.The methodology includes unit root tests that are sensitive to structural breaks and the panel nature of the data: the Cross-sectionally Augmented Dickey-Fuller (CADF) test, Fourier KPSS (FKPSS) and Fourier Panel KPSS (FPKPSS) tests. CADF and FPKPSS are applied to panel data, while the FKPSS test is used at the time series level. The results reveal that the null hypothesis of stationarity is rejected for all series, confirming the existence of a hysteresis effect in unemployment. This effect is particularly pronounced in youth and female unemployment. Additionally, certain regions such as TR31, TR32, TR61, TR71, TR82, TRA1, TRA2, TRB1, TRC2, and TRC3 show higher sensitivity to permanent shocks. These findings underscore the necessity of regionally sensitive and inclusive employment policies.
Keywords: Long-term Unemployment; Youth Unemployment; NUTS-2 Regions; Unemployment Hysteresis; Türkiye